Marvino's league of superheroes - Cosico, Rae Rival (Adarna House, Inc., 2014)
"A museum of toys and superheroes suddenly opens in the town of Majayjay! Unfortunately, Marvino cannot afford the entrance fee at the museum. He contents himself with drawing superheroes outside the museum and showing them to his new friend. One day, the museum doors finally open for Marvino."